The Effect of Feeding Classes On Infants And Children On Mother's Knowledge In Jatinom Village, Klaten District - Anik Sri Martanti; Anik Kurniawati; KH. Endah Widhi Astuti (Yayasan Inspirasi El Burhani, 2023)
Introduction: Improper nutrition practices are the main cause of early happening stunting. Incident malnutrition increases Because of ignorance And the inability of mothers to prepare nutritious food for their children. This ignorance is one of the reasons because there is no supporting information media related to the practice of feeding on child for a mother who has a child Baduta (Lower Two Year). Aims: To determine the effect of PMBA classes (infant feeding and child) towards knowledge clown mothers about feeding practice, baby and child. Methods: This type of research used was pre-experimental with one group pretest–posttest design without a control group. Sampling technique total sampling, obtained a total sample of 48 respondents in the Jatinom Village. Technique analysis used the Wilcoxon test with a level significance of 0.05. Results: Knowledge Mother clown before class PMBA in Ward Jatinom, Klaten with average 9,14 with lowest value 8 and highest 13, standard deviation 1.71. Knowledge after done class PMBA in ward Jatinom is 10.31 with the lowest value of 8 and the highest at 15, the standard deviation is 1.95. Based on analysis bivariate is known to influence class PMBA to knowledge Mother (p=0.000) Conclusion: There is an influence of feeding classes on infants and children on mothers’ knowledge about the practice of feeding classes on infants and children in the Village Jatinom, Jatinom Klaten.